Revisited morphology applied for Systematics of flat wasps (Hymenoptera, Bethylidae) - Lanes, Geane O.; Kawada, Ricardo; Azevedo, Celso O.; Brothers, Denis J. (Zootaxa, 2020)
The world fauna of the flat wasps (Bethylidae) is represented by about 3,000 valid species. The skeletal morphology of bethylids is still not adequately understood and the terminology is generally not standardized between its internal taxa and with other Hymenoptera families. The same scenario exists in most of the families in this order. To address this problem, we describe the external skeletal morphology of Bethylidae. We review the terms used to describe skeletal features in the Hymenoptera in general and a consensus terminology is proposed for Bethylidae, which is linked to the online Hymenoptera Anatomy Ontology. The morphology of the studied specimens is illustrated with photos and line drawings. We also discuss the morphological variation at both subfamilial and generic ranks. Our analyses challenge hundreds of inappropriate, confused or imprecise terms traditionally used for Hymenoptera morphology. As a result, we have applied hundreds of updates of the terminology available online at the Hymenoptera Anatomy Ontology.